2016
DOI: 10.1073/pnas.1605941113
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite pollution nanoparticles in the human brain

Abstract: Biologically formed nanoparticles of the strongly magnetic mineral, magnetite, were first detected in the human brain over 20 y ago [Kirschvink JL, Kobayashi-Kirschvink A, Woodford BJ (1992) Proc Natl Acad Sci USA 89(16):7683-7687]. Magnetite can have potentially large impacts on the brain due to its unique combination of redox activity, surface charge, and strongly magnetic behavior. We used magnetic analyses and electron microscopy to identify the abundant presence in the brain of magnetite nanoparticles tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
627
2
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 834 publications
(675 citation statements)
references
References 37 publications
14
627
2
11
Order By: Relevance
“…Transition metal components such as iron are particularly harmful as they have the potential to produce reactive oxygen species causing inflammation throughout the body (Zhou et al 2003;Birben et al 2012). A recent study by Maher et al (2016) demonstrates that airborne magnetite can enter the brain directly via the olfactory bulb, which can foster Alzheimer disease.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal components such as iron are particularly harmful as they have the potential to produce reactive oxygen species causing inflammation throughout the body (Zhou et al 2003;Birben et al 2012). A recent study by Maher et al (2016) demonstrates that airborne magnetite can enter the brain directly via the olfactory bulb, which can foster Alzheimer disease.…”
Section: Introductionmentioning
confidence: 99%
“…In densely populated areas, one of the most significant source of particles is traffic (1,2). Owing to their small size and complicated chemical and physical characteristics (3)(4)(5)(6), atmospheric particles resulting from traffic emissions pose a significant risk to human health (7)(8)(9)(10)(11)(12), and also contribute to anthropogenic forcing of climate (13,14). Previous research on vehicular emissions has demonstrated the presence of soot and ash (3,15) and solid sub-10-nm core particles (4)(5)(6) in primary emissions from vehicles and engines and their variation, depending on vehicle technologies (4,6), the properties of fuels and lubricant oils (15,16), and driving conditions (15)(16)(17).…”
mentioning
confidence: 99%
“…In September 2016, a surprising discovery was reported by Maher and coworkers [5]. They identified a very high quantity of magnetic crystals in human brain tissues -which had an external, environmental origin.…”
Section: Magnetic Properties Of Brain Tissue and The Approach Of Elecmentioning
confidence: 98%